2023
DOI: 10.1021/acs.energyfuels.3c00072
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Two-Dimensional (2D) Boron Carbonitride and 2D Porous Boron Carbonitride for Excellent Energy Storage and Gas Adsorption Applications

Abstract: The development of two-dimensional (2D) carbon nanosheets and microporous 2D carbon nanosheets with high specific surface area (SSA), large pore volume, and high conductivity is important for energy storage and gas storage applications. Traditional microporous carbon materials have several disadvantages such as low accessibility of active sites and poor mass transport due to large diffusion pathways. The nanometer-thick 2D microporous carbon nanosheets permit easy mass/heat transport, leading to overcoming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…This can be ascribed to its time effectiveness, large‐scale production, high crystallinity, large surface area, and plentiful active sites. [ 120 ]…”
Section: Methods Of Bcn Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…This can be ascribed to its time effectiveness, large‐scale production, high crystallinity, large surface area, and plentiful active sites. [ 120 ]…”
Section: Methods Of Bcn Synthesismentioning
confidence: 99%
“…However, their working potential is limited to near 1.2 V. In studies done by Panda et al, they already demonstrated that redox-active N─ and O─ -functional groups make BCN better candidates for supercapacitor applications. [120] The electron deficiency in the boron atom can attract more OH − ions, producing good supercapacitive performance in aqueous and alkaline electrolytes. Their studies demonstrated that compared to 6.0 M potassium hydroxide (KOH), the KOH-activated BCN performs better in acidic electrolytes such as 1 M sulfuric acid (H 2 SO 4 ) Smaller cations such as (H + ) have acidic electrolytes than larger (K + ) ions having VA-BCNNTAs Ni-Fe-coated SiO 2 /Si substrate Vertically aligned 321.0 F g −1 95% after 1000 cycles.…”
Section: Effect Of Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pore/defect engineering and introducing a complementary high-performance 2D counterpart material can improve the surface area and alleviate the stability issue of both 2D materials, respectively, providing enhanced synergistic interplayed energy storage opportunities [113]. Panda et al obtained hierarchal porous BCNNs (p-BCN) with extremely high SSA (3310.4 m 2 g −1 ) by KOH activation at high temperatures [114]. It was found that the assembled symmetric p-BCN device possessed high energy and power densities (17 W h Kg −1 and 4000 W kg −1 ) with high cycling stability.…”
Section: D Bcn-based Electrode Materialsmentioning
confidence: 99%